The influence of warm-season precipitation on the diel cycle of the surface energy balance and carbon dioxide at a Colorado subalpine forest site - S. P. Burns; P. D. Blanken; A. A. Turnipseed; J. Hu; R. K. Monson (Biogeosciences, 2015)
Precipitation changes the physical and biological characteristics of an ecosystem. Using a precipitation-based conditional sampling technique and a 14 year data set from a 25 m micrometeorological tower in a high-elevation subalpine forest, we examined how warm-season precipitation affected the above-canopy diel cycle of wind and turbulence, net radiation Rnet, ecosystem eddy covariance fluxes (sensible heat H, latent heat LE, and CO2 net ecosystem exchange NEE) and vertical profiles of scalars (air temperature Ta, specific humidity q, and CO2 dry mole fraction χc). This analysis allowed us to examine how precipitation modified these variables from hourly (i.e., the diel cycle) to multi-day time-scales (i.e., typical of a weather-system frontal passage). During mid-day we found the following: (i) even though precipitation caused mean changes on the order of 50–70 % to Rnet, H, and LE, the surface energy balance (SEB) was relatively insensitive to precipitation with mid-day closure values ranging between 90 and 110 %, and (ii) compared to a typical dry day, a day following a rainy day was characterized by increased ecosystem uptake of CO2 (NEE increased by ≈ 10 %), enhanced evaporative cooling (mid-day LE increased by ≈ 30 W m−2), and a smaller amount of sensible heat transfer (mid-day H decreased by ≈ 70 W m−2). Based on the mean diel cycle, the evaporative contribution to total evapotranspiration was, on average, around 6 % in dry conditions and between 15 and 25 % in partially wet conditions. Furthermore, increased LE lasted at least 18 h following a rain event. At night, even though precipitation (and accompanying clouds) reduced the magnitude of Rnet, LE increased from ≈ 10 to over 20 W m−2 due to increased evaporation. Any effect of precipitation on the nocturnal SEB closure and NEE was overshadowed by atmospheric phenomena such as horizontal advection and decoupling that create measurement difficulties. Above-canopy mean χc during wet conditions was found to be about 2–3 μmol mol−1 larger than χc on dry days. This difference was fairly constant over the full diel cycle suggesting that it was due to synoptic weather patterns (different air masses and/or effects of barometric pressure). Finally, the effect of clouds on the timing and magnitude of daytime ecosystem fluxes is described.